Personal Rule in Africa: The Case of Botswana Under General Ian Khama - Seabo, B. (International Conference on Public Administration and Development Alternatives (IPADA), 2018)
Personal rule has been a defining feature of African politics since independence. Plurality politics were shunned by leaders who either assumed power through military coup, liberation struggle or elected but later abolished multiparty politics. For most of the post-independence era, Botswana and Mauritius were an exception to the trend, and Botswana was held in high regard as an example of democracy in Africa. This paper assesses personal rule in Africa using the case of Botswana under the reign of General Ian Khama. It shows how a once celebrated beacon of democracy declined in several fronts due to personal rule type of leadership. The paper argues that although procedural elections and presidential transitions continue to define Botswana’s democracy, the country was governed by 'personal rule' of autocratic type during the reign of General Ian Khama. During Khama’s reign, some elements of personal rule that have characterised some African regimes post-independence were commonplace. Even though Botswana cannot be categorised or placed on the same scale with Africa’s most extreme personal regimes, some indicators of personal rule such as corruption, human rights abuse, and 'big man' politics were the hallmarks of the Khama regime.
Journal article in the International Conference on Public Administration and Development Alternatives 04 - 06 July 2018, Stellenbosch University, Saldahna Bay, South Africa
Keywords: Africa; Autocracy; Botswana; Personal rule; Political regimes; Political leadership -- Africa; Politics -- Military leadership